Characterization of the chloroplast genome of a rare species Polygonatum sp. in China (Asparagaceae, Asparagales) - Zhong, Can (Mitochondrial DNA B Resour, 2020)
Polygonatum (Asparagaceae) is a medicinal and food plant that is naturally distributed in most of countries throughout the temperate Northern Hemisphere. Here we report on the complete chloroplast (cp) genome sequence of a rare species Polygonatum sp. without defoliation in late autumn or winter. The cp genome is 157,696 bp in size and includes two inverted repeat regions of 52,821bp, which is separated by a large single-copy region of 84,359 bp and a small single copy region of 20,516 bp. A total of 132 genes were predicted, including 38 tRNA, 8 rRNA, and 86 protein-coding genes. Phylogenetic analysis placed Polygonatum sp. under the subfamily Nolinoideae of the family Asparagaceae.